Suplementação de tanino de Acacia mearnsii em rações para frangos de corte - Godoy, Guilherme Librelotto de (2023)
Due to the pressure to antibiotics removal from poultry production, the search for natural additives that perform a similar function is growing. In this reality, tannin from Acacia mearnsii is an alternative to antibiotics due to its antimicrobial effect. However, tannins do not have a history of use in poultry nutrition due to its anti-nutritional effects that induce to poor performance. However, recent technological advances demonstrate that these effects can be avoided, since they are closely related to the source and dosage of tannin used, animal category and health status. In view of this, the present study was conducted at the UFSM Poultry Laboratory with the objective of evaluating the effects of supplementation of increasing levels of tannins from Acacia mearnsii for broiler chickens submitted to an experimental intestinal challenge with Clostridium perfringens. A total of 1620 day-old broiler chicks were divided into 6 treatments with 10 replicates of 27 birds each. Treatments consisted of non-challenged control, challenged control, and the challenged control fed diets supplemented with 300, 500, 700, or 900 mg/kg of Acacia mearnsii tannin. The challenge was done with a cocci vaccine on day 1 and oral gavage with C. perfringens on days 11, 12, and 13. Performance was evaluated weekly for 43 days of age. At 21 days, blood was collected for biochemical analysis and intestinal permeability was analyzed with fluorescein isothiocyanate-dextran (FITC-d) as marker, in addition to digesta collection to determine nutrient digestibility, and jejunum sample for morphometrics. At 28, 35 and 43 days, litter quality and footpad dermatitis were analyzed. On day 44, broilers were slaughtered for carcass evaluation and thigh samples were collected for lipid oxidation during 6 months of storage at - 20ºC. Data were subjected to analysis of variance using SAS, means were compared using the Tukey's test (P<0.05), and linear and polynomial quadratic regression models. Decreased performance, blood parameters, and higher intestinal permeability were observed in challenged broilers compared to non-challenged (P<0.05). Tannin supplementation caused a quadratic increase in weight gain (WG), improvement in feed conversion (FCR) and a linear decrease in lipid oxidation of meat (P<0.05). Optimal supplementation was 310, 444, 466, 528 mg/kg of tannin for BWG, FCR, intestinal permeability, and villus height, respectively (P<0.05). Protein digestibility improved at 374 mg/kg tannin (P<0.05). The results indicated that low levels of tannin supplementation in the broiler diet promote improvements in performance, digestibility and intestinal health in challenge, while increasing levels of tannin retard meat lipid oxidation.